Study of Mouse Deer and Snail Characters in Fable (Deconstruction Approach) - Izhar Izhar (Future Science, 2021)
ABSTRACT The presence of the mouse deer and snail fable is considered to contribute in education field. The character of the mouse deer with its strengths and the snail with its weaknesses brings its own spirit to the reader that the irrationality of the weak can defeat the strong is acceptable logic. Thus, the strong mouse deer is judged as a loser and the weak snail is judged as a hero by the readers. In fact, in a certain sense, the meaning of an event conveyed through the characters of the story can be inversely to the reader's interpretation so far. The objectives of this study were (1) to describe the characters of the mouse deer and snail in deconstruction studies; and (2) to describe the relevance of deconstruction studies with critical thinking activities in the independent learning era. The research was a descriptive qualitative research based on research studies using Derrida's deconstruction. Data analysis was carried out in stages, namely: reading repeated texts carefully so that the original context and reception context were found, tracing binary opposition, and presenting other logic or other perceptions. The results of the study shows that (1) the snail character who has been predicted to be a good character can be considered an arrogant and fraudulent character. Meanwhile, the mouse deer figure who has been regarded as an arrogant figure can be considered an honest and kind character, and (2) the deconstruction study method is relevant to critical thinking activities in the independent learning era.